Derajat Asam Tepung Sagu yang Dijual di Pasar Tradisional Kecamatan Mandonga Kota Kendari - Balaka, Sukina; Rasmaniar, Rasmaniar; Iswardani, Octaldina (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2016)
Background: One of the local food in Southeast Sulawesi is Sinongi. Sinonggi is the staple food of the tribe Tolaki. The raw material for making Sinonggi is sago flour. Generally sago flour in Southeast Sulawesi prepared traditionally methodes so the sanitaries is not enough for mantain contaminant of microbes producing organic acid which causing deteriration of sago and the impact of product become changing in colour, aroma, taste. Objective: to determine the degree of acidity sago as the raw materials for making sinonggi in traditional markets Mandonga, Kendari city.Method: Types of research design is descriptive surveys studies. The research was done on November to Desember 2014. The sample of this research are sago starch were sold in traditional markets Mandonga of Kendari City as many as 12 samples were Purposive Sampling. Type of analysis included: forms of sago flour and the degree of acidity of sago flour (SNI 3729: 2008) Result: The results showed that of the 12 samples of sago flour 7 samples (67%) are wet sago flour form, and Nine samples (75%) have a degree of acidity did not meet predetermined requirements in SNI. Conclusion: Most of the samples have a degree of acidity did not meet predetermined requirements in SNI 3729: 2008